Keruntuhan Peradaban Suatu Masyarakat dalam Perspektif Al-Qur’an - Rianto Hasan (Jurnal Studi Al-Quran, 2019)
Al-Qur'an as a guide book through the concept of social laws seeks to encourage a positive transformation in human social life so that its function as a hudan can be realized. The social principles discussed in the Qur'an among other are those related to the dogmas that regulate the existence or period limit of human civilization. The doctrine is implied by this holy book through the terminology of ajal which is framed with the word ummah in QS. al-A‘raf 7: 34. The problem then arises regarding how to determine the meaning of ajal. This article is then written to address the problem that can be solved based on the mechanism of the epistemological framework of exegesis, using the syntagmatic-paradigmatic semiotic analysis of Ferdinand De Saussure. From the research that has been done, it is understood that the terminology of the collapse of the society’s civilization which is contained in the verse can be interpreted with the following senses: 1) It expresses the meaning of the population destruction caused by punishment; 2) It is interpreted as the phase of the end of the power/sovereign order of a nation as part of the characteristics of the community civilization entity. Generally, it was concluded that the trigger for the end of the civiliztion existence was caused by the fading of the religiosity in their lives which influenced the pattern of community interaction which then caused various kinds of social inequality. The disequilibrium that arises in the midst of this social ecosystem then ends the glory period of the civilization.